The Impact of 4IR technologies in Visual Art - Xaba, Siyanda; Fang, Xing; Shah, Dhaneshwar; Mugerwa, Ibrahim (Journal of History Culture and Art Research, 2022)
The Fourth Industrial Revolution (4IR) will have a great impact on society with technologies that are said to revolutionize industries. Research tells us that technologies such as Artificial Intelligence (AI), Internet of Things (IoT), Cyber-Physical Systems (CPS), robotics, and 3D printing will change the workplace, allowing greater performance and productivity. Extensive research in this discipline including manufacturing, employment, education, ICT, healthcare, and smart factories investigated the attitude of employees on the adoption of new technologies to simplify certain work professions and the results indicate that these technologies are capable of improving the way of living. There is a dearth of research that looks into the impact of 4IR in Visual Art. We have been told that the creative sector will be at forefront of the 4IR, however, we have no idea what technologies will be used in Visual Art in the 4IR. Therefore, the study aims to bridge this gap by discussing the impact of 4IR technologies in Visual Art. The study uses a practice-led method, focusing on the creative process of digital art technologies such as Autodesk Sketchbook, Deep Dream Generator, and Rhinoceros.